ABC1K1/PGR6 kinase: a regulatory link between photosynthetic activity and chloroplast metabolism. (28th December 2013) - Martinis, Jacopo; Glauser, Gaétan; Valimareanu, Sergiu; Stettler, Michaela; Zeeman, Samuel C.; Yamamoto, Hiroshi; Shikanai, Toshiharu; Kessler, Felix
Summary Arabidopsis proton gradient regulation (pgr) mutants have high chlorophyll fluorescence and reduced non‐photochemical quenching (NPQ) caused by defects in photosynthetic electron transport. Here, we identify PGR6 as the chloroplast lipid droplet (plastoglobule, PG) kinase ABC1K1 (activity of bc1 complex kinase 1). The members of the ABC1/ADCK/UbiB family of atypical kinases regulate ubiquinone synthesis in bacteria and mitochondria, and impact various metabolic pathways in plant chloroplasts. Here, we demonstrate that abc1k1 has a unique photosynthetic and metabolic phenotype that is distinct from that of the abc1k3 homolog. The abc1k1/pgr6 single mutant is specifically deficient in the electron carrier plastoquinone, as well as in β–carotene and the xanthophyll lutein, and is defective in membrane antioxidant tocopherol metabolism. After 2 days of continuous high light stress, abc1k1/pgr6 plants suffer extensive photosynthetic and metabolic perturbations, strongly affecting carbohydrate metabolism. Remarkably, however, the mutant acclimates to high light after 7 days together with a recovery of carotenoid levels and a drastic alteration in the starch‐to‐sucrose ratio. Moreover, ABC1K1 behaves as an active kinase and phosphorylates VTE1, a key enzyme of tocopherol (vitamin E) metabolism in vitro. Our results indicate that the ABC1K1 kinase constitutes a new type of regulatory link between photosynthetic activity and chloroplast metabolism.